TINGKAT LOYALITAS MAHASISWA ATAS JASA PENDIDIKAN DI PERGURUAN TINGGI - Wahyuningsih, Sri Endah (Lembaran Ilmu Kependidikan, 2007)
A loyalty is needed for the survival of study program or department in a highereducation as a service industry. The loyalty of students can give a positiverecommendation to other parties to motivate prospective customers to use the service.It is more effective as a means of promotion and reduces the marketing cost. Theobjective of the study is to describe the students’ loyalty to the Department of ServiceProduction Technology of the Faculty of Engineering of Semarang State University.The research is descriptive. The subjects of the research were students of Departmentof Service Production Technology of the Faculty of Engineering of Semarang StateUniversity. The students are undergraduate students majoring in Family WelfareEducation concentrating on Fashion and Culinary. Another group of students wereDiploma Tree students of Service Production Technology concentrating on Fashionand Culinary. The number of the sample was 150 determined by iteration formula.The data were collected with a questionnaire and analyzed with descriptivepercentage. The result showed that 76% was moderately loyal, 22% highly loyal, andonly 2% were not loyal. Based on the result of the research, it is suggested that theDepartment improve moderately loyal students into highly loyal through a betterservice such as: building, practicum tools, empathy, and awareness.Kata kunci: loyalitas, mahasiswa, jasa pendidikan Perguruan Tinggi